Importance of nurses for good therapeutic adherence of hypertensive patients in primary care (Research, Society and Development, 2023)
Systemic arterial hypertension is a chronic comorbidity that is characterized by the potential to generate metabolic, functional and structural alterations, and increase the risk for cardiovascular diseases. The treatment aims to reduce the morbidity and mortality of patients, and can be carried out with medication or non-medication. The family's basic care is characterized as a gateway for disease prevention and health promotion, and the nurses in these units are able to provide care, raise risk factors and identify diseases, having the opportunity to improve the patient's quality of life. In this sense, this study aims to describe the importance of nurses for good therapeutic adherence of patients with hypertension. This is an integrative review carried out in the databases: SCIELO, LILACS, MEDLINE and BdENF through the descriptors “Hypertension”, “Adherence” and contributes to better adherence to “Nursing” therapy. The search totaled 10 articles that showed that the nurse welcomes the hypertensive patient, provides guidance, health education, active search, develops bonds and uses technologies that contribute to better adherence to therapy. It is concluded that the actions carried out by nurses in primary care have positive impacts on the greater adherence of hypertensive patients to the therapeutic plan, as it generates a feeling of appreciation, encourages self-care and involves the patient in their therapeutic plan.